Development Design for Outcomes Based Learning tools in Merdeka Curriculum in Schools and Universities - Tasya Amelia Putri Siregar; Muhammad Irfansyah Siregar; Siti Halimah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The objective of this study is to identify the curriculum development design utilized in the creation of learning tools within the context of both the School and Merdeka curricula. The learning tools produced at each of these institutions are designed with an emphasis on outcome-based learning, with the objective of developing students' abilities to support the learning process.This study employs a qualitative methodology with a library research approach, utilizing relevant literature sources and assisting research. The findings of this study indicate that the competencies referenced in the learning tool must be adjusted to align with the learning outcomes for each phase. This implies that each competency generates outcome-based learning (OBE) within the context of each learning outcome through the use of learning tools. At the school level, the resulting OBE is CP (Learning Outcomes), while at the university level, the resulting OBE is CPL (Graduate Study Program Outcomes).